STRATEGI PENGEMBANGAN USAHA ULIN COFFEE ROASTERY - Ervina Mela; Via Wulandari; Lintang Arista (Institute of Computer Science (IOCS), 2023)
Ulin Coffee Roastery is a company in coffee roasting. This company has various obstacles in its business which need to be resolved by formulating an appropriate business development strategy. The aim of this research is to formulate a business development strategy at Ulin Roastery using SWOT analysis. Interviews and observations were carried out to obtain data as a basis for formulating strategies. Business development strategies include maintaining product price stability, carrying out promotions at special events, participating in training and guidance carried out by local governments including training on marketing, intensifying promotions through social media, including production dates on product packaging, increasing quality control activities throughout the process, optimizing the partner network, including increasing cooperation with farmer groups in terms of providing raw materials, maximizing product branding and updating production tools and machines.